Vulvar Paget disease secondary to high-grade urothelial carcinoma with underlying massive vascular embolization and cervical involvement: case report of unusual presentation - Walquiria Quida Salles Pereira Primo; Guttenberg Rodrigues Pereira Primo; Dunya Bachour Basilio; Karime Kalil Machado; Jesus Paula Carvalho; Filomena M. Carvalho (BMC, 2019)
Abstract Background Vulvar extramammary Paget disease is a rare chronic condition, that presents with non-specific symptoms such as pruritus and eczematous lesions. Because most of these lesions are noninvasive, the distinction between primary and secondary Paget disease is crucial to management. Case presentation We report an unusual case of vulvar Paget disease associated with massive dermal vascular embolization, cervicovaginal involvement and metastasis to inguinal and retroperitoneal lymph nodes. The intraepithelial vulvar lesion had a classical appearance and was accompanied by extensive component of dermal lymphovascular tumor emboli, similar to those observed in inflammatory breast carcinoma. Immunohistochemical analysis revealed that the lesion was secondary to high-grade urothelial cell carcinoma. The patient had a history of superficial low-grade papillary urothelial carcinoma of the bladder, which had appeared 2 years before the onset of vulvar symptoms. Conclusions Eczematoid vulvar lesions merit careful clinical examination and biopsy, including vulva mapping and immunohistochemistry. The information obtained may help to define and classify a particular presentation of Paget disease. Noninvasive primary lesions do not require the same aggressive approaches required for the treatment of invasive and secondary disease.